Optimum level of spray-dried blood meal in phase II diet - L J Kats; Jim L Nelssen; Michael D Tokach; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1992)
A total of 744 pigs (initially 12.8 lb and 22 d of age) was used in a 28 d trial to determine the effects of increasing levels of blood meal in the phase II (d 7 to 28) diet. Pigs were allotted by sex and weight and placed in pens containing 13 to 14 pigs each. A common phase I diet was fed for the first 7 days postweaning. The phase I diet contained 37.5% dried whey and 7.5% porcine plasma and was formulated to contain 1.5% lysine. After the phase I period, pigs were assigned to one of six dietary treatments that contained 10% dried whey and either 0, 1, 2, 3, 4, or 5% spray-dried blood meal. These diets were fed for the entire phase II period (d 7 to 28 postweaning). Phase II diets were formulated to contain 1.25% lysine and a minimum of .68% isoleucine and .30% methionine. During phase I (d 0 to 7), average daily gain, average daily feed intake, and feed efficiency (FIG) were .34 lb, .38 lb, and 1.28, respectively. During phase II (d 7 to 28), quadratic improvements occurred in average daily gain, average daily feed intake, and feed efficiency, with optimum performance achieved at approximately the 2% inclusion rate of spray-dried blood meal. Therefore, the results of this trial indicate that the optimal level of spray-dried blood meal in the phase II diet is approximately 2%.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Starter; Blood meal; Performance